2015
DOI: 10.1002/hbm.23033
|View full text |Cite
|
Sign up to set email alerts
|

Cortical localization of phase and amplitude dynamics predicting access to somatosensory awareness

Abstract: Neural dynamics leading to conscious sensory perception have remained enigmatic in despite of large interest. Human functional magnetic resonance imaging (fMRI) studies have revealed that a co-activation of sensory and frontoparietal areas is crucial for conscious sensory perception in the several second time-scale of BOLD signal fluctuations. Electrophysiological recordings with magneto- and electroencephalography (MEG and EEG) and intracranial EEG (iEEG) have shown that event related responses (ERs), phase-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
46
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 31 publications
(53 citation statements)
references
References 106 publications
(220 reference statements)
5
46
1
Order By: Relevance
“…The statistical threshold for the spatial extent test was set at p < .05, family-wise error (FWE)-corrected for multiple comparisons over the whole brain when the height threshold was set at p < .001 The human S1 is involved in various aspects of conscious tactile perception, such as the detection and localization of stimuli (Auksztulewicz et al, 2012;Blankenburg et al, 2006;Hirvonen & Palva, 2016;Meador et al, 2002). Brain activation during the velvet hand illusion (strong illusion relative to weak illusion, Si -Wi) in the group analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The statistical threshold for the spatial extent test was set at p < .05, family-wise error (FWE)-corrected for multiple comparisons over the whole brain when the height threshold was set at p < .001 The human S1 is involved in various aspects of conscious tactile perception, such as the detection and localization of stimuli (Auksztulewicz et al, 2012;Blankenburg et al, 2006;Hirvonen & Palva, 2016;Meador et al, 2002). Brain activation during the velvet hand illusion (strong illusion relative to weak illusion, Si -Wi) in the group analysis.…”
Section: Discussionmentioning
confidence: 99%
“…As activity in the PO is associated with the magnitude of the texture percept (Eck et al, 2016;Kitada et al, 2005), the bottom-up processing of texture information from the S1 to PO may occur (Hsiao, Johnson, & Twombly, 1993;James, Kim, & Fisher, 2007;Sathian, 2016;Sathian et al, 2011). Other studies have also examined the neural substrates associated with conscious detection of tactile stimuli (Auksztulewicz, Spitzer, & Blankenburg, 2012;Hirvonen & Palva, 2016;Linkenkaer-Hansen, Nikulin, Palva, Ilmoniemi, & Palva, 2004;Meador et al, 2017;Meador, Ray, Echauz, Loring, & Vachtsevanos, 2002;Monto, Palva, Voipio, & Palva, 2008). Previous studies regarding tactile illusions have demonstrated that S1 is associated with illusory mislocalization of tactile sensations (Blankenburg et al, 2006;Bufalari, Di Russo, & Aglioti, 2014;Chen, Friedman, & Roe, 2003).…”
mentioning
confidence: 99%
“…Furthermore, sustained phase locking of ongoing neuronal activity to somatosensory stimulus and a transient increase in the strength of oscillation amplitudes predicted also whether weak stimuli presented at the threshold of detection were consciously perceived (Hirvonen and Palva 2016;Palva et al 2005b) (Fig. 1a-b).…”
Section: Does Local Synchrony Reflect Sensory Perception?mentioning
confidence: 93%
“…Several methods such as beamformers (Gross et al 2001), low resolution electromagnetic tomography (LORETA) (Pascual-Marqui et al 2011), and minimumnorm estimation (MNE) (Hamalainen and Ilmoniemi 1994;Lin et al 2006) have been developed for source reconstruction. Indeed, a large body of source reconstruction-based MEG studies have shown that the amplitudes of local cortical oscillations, which reflect synchronization in the local neuronal populations, are correlated with attention (Händel et al 2011;Rouhinen et al 2013;Zumer et al 2014), perception (Haegens et al 2011;Hirvonen and Palva 2016), and WM (Bonnefond and Jensen 2012;Honkanen et al 2015;Palva et al 2011;Roux et al 2012) and hence with many distinct cognitive functions.…”
Section: Challenges In the Analyses Of Synchrony Frommentioning
confidence: 99%
See 1 more Smart Citation